Lifespan normative data on rates of brain volume changes - Battaglini, Marco; Gentile, Giordano; Luchetti, Ludovico; Giorgio, Antonio; Vrenken, Hugo; Barkhof, Frederik; Cover, Keith S; Bakshi, Rohit; Chu, Renxin; Sormani, Maria Pia; Enzinger, Christian; Ropele, Stefan; et al. (Neurobiology of aging, 2019)
We provide here normative values of yearly percentage brain volume change (PBVC/y) as obtained with Structural Imaging Evaluation, using Normalization, of Atrophy, a widely used open-source software, developing a PBVC/y calculator for assessing the deviation from the expected PBVC/y in patients with neurological disorders. We assessed multicenter (34 centers, 11 acquisition protocols) magnetic resonance imaging data of 720 healthy participants covering the whole adult lifespan (16-90 years). Data of 421 participants with a follow-up > 6 months were used to obtain the normative values for PBVC/y and data of 392 participants with a follow-up <1 month were selected to assess the intrasubject variability of the brain volume measurement. A mixed model evaluated PBVC/y dependence on age, sex, and magnetic resonance imaging parameters (scan vendor and magnetic field strength). PBVC/y was associated with age (p < 0.001), with 60- to 70-year-old participants showing twice more volume decrease than participants aged 30-40 years. PBVC/y was also associated with magnetic field strength, with higher decreases when measured by 1.5T than 3T scanners (p < 0.001). The variability of PBVC/y normative percentiles was narrower as the interscan interval was longer (e.g., 80th normative percentile was 50% smaller for participants with 2-year than with 1-year follow-up). The use of these normative data, eased by the freely available calculator, might help in better discriminating pathological from physiological conditions in the clinical setting.
Keywords: dospělí; Female; zobrazování trojrozměrné; Imaging, Three-Dimensional; Adult; ženské pohlaví; mladý dospělý; Organ Size; Aging; Adolescent; difuzní magnetická rezonance; Multicenter Studies as Topic; lidé; Aged, 80 and over; mozek; dlouhověkost; atrofie; retrospektivní studie; multicentrické studie jako téma; velikost orgánu; Male; Brain volume; Aged; Atrophy; Brain; Young Adult; stárnutí; Diffusion Magnetic Resonance Imaging; Normative data; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; MRI; Longevity; Retrospective Studies; Middle Aged; mladiství; Humans